Problematic aspects of staffing the domestic pharmacy segment in the context of pharmaceutical safety - N. O. Tkachenko; O. B. Pankevych; B. P. Hromovyk (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The aim of the work is to identify problematic issues of human resource potential in the domestic pharmacy segment from the point of view of pharmaceutical safety.